2015
DOI: 10.1123/jis.2014-0093
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships between Passion and Attitudes Toward Performance Enhancing Drugs in Canadian Collegiate Sport Contexts

Abstract: The purpose of this study was to explore relationships between passion and attitudes toward performance enhancing drugs (PEDs). Participants were 587 male and female varsity and coed intramural athletes from four Southern Ontario universities. Athletes completed the passion scale (Vallerand et al., 2003) and the performance enhancement attitudes scale (Petróczi, 2006). Full sample regression analyze revealed that higher scores on obsessive passion items were associated with more permissive attitudes toward PED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Bélanger and colleagues (2019) also show that people who obsessively engage in the passionate activity tend to favor counterfinal means. Accordingly, athletes obsessively passionate about their sport display more permissive attitudes towards PES, as opposed to harmoniously passionate athletes, who see sport as a more balanced addition to their life [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bélanger and colleagues (2019) also show that people who obsessively engage in the passionate activity tend to favor counterfinal means. Accordingly, athletes obsessively passionate about their sport display more permissive attitudes towards PES, as opposed to harmoniously passionate athletes, who see sport as a more balanced addition to their life [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Informants in the current study reported that, at the professional level, 'anything goes.' In a broad sense, 'urgency' here might relate to what has been termed 'obsessive passion' (Wilson & Potwarka, 2015).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…From an athletic participant perspective on the fairness of drug testing, Wilson and Potwarka (2015) studied how an athlete's passion predicted attitudes toward PEDs. The study showed athletes with more obsessive passion toward athletics had more positive attitudes toward using PEDs.…”
Section: Approaches To Drug Testingmentioning
confidence: 99%